THE EFFECT OF JOB CHARACTERISTIC, WELFARE AND WORK ENVIRONMENT TO EMPLOYEE PERFORMANCE AT PT. FEDERAL INTERNATIONAL FINANCE MANADO - Tulandi, Christy; Mandey, S. L.; Walangitan, Mac Donald (Universitas Sam Ratulangi, 2015)
Job characteristic is the determinant of the fit between person with a particular line of work that explored. Welfare is the remuneration provided by the company based on the company rules. Work environment is physical and non-physical workplaces that have direct effect on employee. The purpose of this study is to determine the influence of Â job characteristic, welfare and work environment on employee performance at PT. Federal International Finance Manado. The population in the study is 65 employees with a total of 65 samples and sampling technique used is saturated sampling method. Data analysis is using multiple regression with F and t test. The results show job characteristic, employee welfare and work environment have positive effect, either simultaneously or partially on employee performance. We recommend that the management of PT. Federal International Finance, need to improve the employee performance through an increasing in the variation of job characteristic, employee welfare and also the improvement of work environment at the company. Keywords: job characteristic, employee welfare, work environment, employee performance